2021
DOI: 10.1002/maco.202112745
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dislocation on sour corrosion of carbon steel in a low H2S sour environment

Abstract: The influence of dislocation on corrosion of low alloy steel in a low H2S sour corrosion environment was investigated experimentally (immersion corrosion test and polarization measurement) and theoretically (ESM‐RISM simulation). The results showed that dislocation increases corrosion weight loss by promoting the anodic dissolution reaction. The Fe atom solubilities of two kinds of Fe slab models simulating conditions with/without lattice defects were evaluated, and the high Fe solubility of the model with lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…Dunlop [ 89 ] observed that the applied cathodic polarization was able to inhibit the propagation of cracks in steel formed in environment containing low 0.01 atmospheric partial pressure of H 2 S. Thus, Yamane et al [ 6 ] proposed a model for SSC whereby initiation stage of SSC was dominated by localized anodic dissolution at the tip of the corrosion pit followed by HE as the dominant mechanism during the propagation stage of SSC. [ 37 ] Based on this proposed model, Samusawa et al [ 90 ] also went on to analyze the depth of corrosion pit within pipeline steels exposed to 0.15 bar H 2 S partial pressure under different applied stress and concluded that the increase in stress concentration increases the dislocation density and thus the corrosion rate, therefore increasing the depth of corrosion pit. This in turn further increases the localized stress concentration which promotes HE.…”
Section: Environmental Factors Influencing Sscmentioning
confidence: 99%
See 1 more Smart Citation
“…Dunlop [ 89 ] observed that the applied cathodic polarization was able to inhibit the propagation of cracks in steel formed in environment containing low 0.01 atmospheric partial pressure of H 2 S. Thus, Yamane et al [ 6 ] proposed a model for SSC whereby initiation stage of SSC was dominated by localized anodic dissolution at the tip of the corrosion pit followed by HE as the dominant mechanism during the propagation stage of SSC. [ 37 ] Based on this proposed model, Samusawa et al [ 90 ] also went on to analyze the depth of corrosion pit within pipeline steels exposed to 0.15 bar H 2 S partial pressure under different applied stress and concluded that the increase in stress concentration increases the dislocation density and thus the corrosion rate, therefore increasing the depth of corrosion pit. This in turn further increases the localized stress concentration which promotes HE.…”
Section: Environmental Factors Influencing Sscmentioning
confidence: 99%
“…This in turn further increases the localized stress concentration which promotes HE. [90] Some studies have also shown a threshold potential at which HE will dominate over the anodic dissolution process in facilitating crack growth rate in samples electrochemically charged with hydrogen. [10,11] In order to identify the dominating mechanisms, a common method involves carrying out linear sweep voltammetry of the metal-electrolyte electrochemical system at different rates to identify the regions of anodic dissolution, cathodic HE, or a mixture of both within the polarization curve at which SSC crack propagates.…”
Section: Transition From Anodic Dissolution To Hementioning
confidence: 99%
“…The authors examined the SSC mechanism in the low H 2 S partial pressure condition of 0.15 bar for the general X65 grade (YS ≥ 450 MPa) material as a low alloy steel line pipe, and clarified that the transgranular microcrack formation process is the anodic dissolution control based on the APC mechanism. 28) In addition, it was clarified that the local dissolution was promoted by plastic deformation 29) and higher material hardness, 30) and it was estimated from compact tension (CT) test with pre-crack that the initiation and propagation process of SSC crack was caused by HE mechanism. 16) However, since there exist multiple factors such as microscopic structural morphology and crystal orientation distribution of bainite structure, microscopic elasto-plastic deformation of tensile surface with increasing applied stress, and sour environmental conditions such as H 2 S partial pressure and pH, it is not clear how these factors relate to the initial corrosion pit and groove formation process and SSC crack initiation and propagation process.…”
Section: Sulfide Stress Cracking (Ssc) Of Low Alloy Linepipe Steels I...mentioning
confidence: 99%
“…用いられる 1) 。ラインパイプの特性としては,強度,靭性に 加えて耐腐食性が求められる 2) 。特に,硫化水素(H 2 S)ガ スや炭酸(CO 2 )ガス等腐食性ガスを含んだ湿潤サワー環 境において,水素誘起割れ(HIC)や硫化物応力腐食割れ (SSC)に対して十分な耐性が必要となる [3][4][5] 。 パイプライン操業時にはパイプ内面の周方向に引張応 力が負荷し,サワー環境においては SSC 発生による破壊事 故の懸念がある。SSC は主に材料 [6][7][8]) ,サワー環境 9,10) ,負 荷応力 11,12) bar 以上では全面腐食主体となり,H 2 S 濃度の増加に伴い水 素侵入量が多くなり 18,19) ,SSC き裂発生は HE 機構主体で あった。このように H 2 S 分圧の環境に応じて,APC 機構と HE 機構の寄与度が異なっていることが示唆された。 従 来 研 究 [19][20][21][22] で は,低 合 金 鋼 の SSC は HE の 一 種 と 見 なされている。一方,低濃度 H 2 S 環境の先行研究 [23][24][25][26][27] にお いて,その前駆過程として APC の強い寄与が示唆されて いる。例えば,Yamane ら 24) SSC 機構を検討し,腐食ピット・グルーブ形成過程が APC 機構に基づくアノード溶解支配であること 28) を明らかに した。また,その局部溶解が塑性変形 29) や材料高硬度化に より促進されること 30)…”
Section: 天然ガス輸送用パイプラインには厚板鋼板を素材として 造管され製造される低合金鋼ラインパイプ(Uoe 鋼管)がunclassified